Darkness before dawn - Draper, Sharon M. (Sharon Mills) (New York : Atheneum Books for Young Readers, 2001)
Recovering from the recent suicide of her ex-boyfriend, senior class president Keisha Montgomery finds herself attracted to a dangerous, older man
Accelerated Reader/Renaissance Learning
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Rape -- Juvenile fiction; African Americans -- Juvenile fiction; Fiction; Juvenile works